SISTEM PENUNJANG KEPUTUSAN KELULUSAN PESERTA PRAJABATAN MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING PADA PUSAT PENGEMBANGAN TENAGA KEPENDIDIKAN - Ibnu Rusdi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
Development and human resource development (HRD ) as the challenges and demands in the era of globalization which makes change very rapidly, an urgent need. Human Resource Development conducted and produced through education and training programs ( training ) which is a very strategic way of improving the quality of human and dignity, dignity and well-being. In the process of training in Pusbangtendik Pre-service participants consisted of 3 types of them; leadership training ( Echelon 3 and 4); Pre-service training and technical training. All employees who would be prepared civil servants in order to better understand the procedures and policies. SAW method is often also known as the term method weighted summation. The basic concept of the method SAW is looking for a weighted sum of the rating performance at each alternative on all attributes. SAW method requires a process of normalization a decision matrix (X) to a scale that can be compared with all the rating alternatives which exist.